STUDY ON THE POTENTIAL TO ABSORB HEAVY METAL (FE, CU, MN) IN CONTAMINATED WATER BY Centella asiatica - Thi Ngoc Bich, Nguyen; Van Chung, Nguyen; Thi Thuy An, Thai; Phu Tuan, Le; Thi Kim Oanh, Vu (Journal of Forestry Science and Technology, 2020)
Centella asiatica has advantages in heavy metals treatment in soil and water. In Vietnam, native plants have the ability to treat environmental pollution very well. Numerous studies have demonstrated the ability of Centella asiatica to handle heavy metals in soil. However, the research team wanted to confirm their adaptability in the water. This study carried out the potential to absorb some heavy metals as Fe, Cu, Mn by using Centella asiatica and showed the remarkable results. When the heavy metal concentrations were changed, the removal efficiencies also were changed respectively. This research conducted to analyze heavy metal concentration in contaminated water by method UV-VIS and in vegetable by method Atomic Absorption Spectroscopy (AAS). The highest amounts of Fe, Cu and Mn found in vegetable were 9 mg/kg, 15 mg/kg and 3 mg/kg, respectively. During the development, the Centella asiatica turned increase the pH level, helped the solids settle more quickly and increased the heavy metal treament efficiencies. In all of experiment steps, there was no addition any nutrition for support the Centella asiatica growing. Therefore, this was a new trend to continuously research the potential to treat heavy metal in water using Phytoremediation (Phytoremediation technologies use plants to treat hazardous contaminants in soil, air, and water).